Comparison of Commissive Acts between University of Oxford’s and Universitas Indonesia’s Prospectuses - Fajriyati Waibah Mosambonga; Issy Yuliasri; Abdurrachman Faridi (Yayasan Visi Intan Permata, 2022)
This study aimed to compare Oxford University (OU) as a native English speaker and Universitas Indonesia (UI) as a non-native English speaker in presenting commissive acts in their university prospectus to see their similarities and differences. This study used the descriptive qualitative method. The data were an English-written prospectus from OU, The World's Best University and UI, The Best Indonesian University in 2020, based on the 2020 World University Rankings by Times Higher Education (THE). Specifically, data were taken only from forty-nine courses in Undergraduate Programs from each prospectus. Data were analyzed using six types of commissive acts instruments according to Searle, (1976), namely Promise, Threaten, Guarantee, Refuse, Volunteer, and Offer supported with (IFIDs) and Felicity Conditions. Data were analyzed by identifying the types of commissive acts, classifying, comparing, interpreting, and concluding. This study found four similarities; both only presented three types of commissive acts such as Promise, Offer, and Guarantee. Both dominant presented the Guarantee type. Both tend to present commissive acts implicitly. For Promise and Guarantee, both do not present them explicitly. Three differences were; OU presented more commissive acts (312), while UI only (193). On the Promise type, OU tends to address its readers using (you), while UI used (students). On the Offer type, OU only presented it explicitly (27) times, while UI did it explicitly (17) and implicitly (3) times. The results of this study are expected to provide additional information regarding the proper use of commissive acts to attract readers' interest.